2019
DOI: 10.37761/rsqp.v85i4.261
|View full text |Cite
|
Sign up to set email alerts
|

Pretratamiento E Hidrólisis Enzimática De La Cascarilla De Arroz

Abstract: El presente estudio evaluó la hidrólisis de la cascarilla de arroz, mediante el pretratamiento alcalino-peróxido, ácido-peróxido y silicato-peróxido, seguido de hidrólisis enzimática utilizando celulasas, con alto nivel de β-glucosidasas y hemicelulasas. Los pretratamientos fueron realizados variando las concentraciones del medio alcalino (0, 2, 4 y 6 % p/v), ácido (0, 5, 10 y 15 % v/v) y silicato (0, 5, 10 y 15 % p/v) en concentraciones variables de peróxido (0, 5, 10 y 15 % v/v). La hidrólisis enzimática fue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 20 publications
0
1
0
Order By: Relevance
“…High temperatures seem to favor the release of sugars from the CPH and additional studies would be necessary to determine whether in harsh conditions inhibiting substances that may affect subsequent fermentation processes are generated. Indeed, recent studies reported that high temperature pretreatments of lignocellulose can generate furfurals and 5-hydroxymethylfurfural, which are inhibitory compounds for a variety of microorganisms [69]. In addition, high temperatures for extended periods could be considered uneconomical and not environmentally friendly.…”
Section: Hydrogen Peroxide (H 2 O 2 ) Pretreatment Of Cphmentioning
confidence: 99%
“…High temperatures seem to favor the release of sugars from the CPH and additional studies would be necessary to determine whether in harsh conditions inhibiting substances that may affect subsequent fermentation processes are generated. Indeed, recent studies reported that high temperature pretreatments of lignocellulose can generate furfurals and 5-hydroxymethylfurfural, which are inhibitory compounds for a variety of microorganisms [69]. In addition, high temperatures for extended periods could be considered uneconomical and not environmentally friendly.…”
Section: Hydrogen Peroxide (H 2 O 2 ) Pretreatment Of Cphmentioning
confidence: 99%